Quality of Life of Elderly Farmers in Chainat Province: An Analysis Using United Nations Quality of Life Indicators - Sapbruangthong, Litsak; Subruangthong, Salinee; Somwang, Kissawat (Rajapark Journal, 2025)
This research aimed to 1) assess the quality of life of elderly rice farmers in Chainat Province based on the United Nations’ Quality of Life Indicators and 2) compare their quality of life according to personal factors including gender, age, marital status, chronic illness, income, debt, and total farming area. The sample consisted of 412 elderly rice farmers, selected using multi-stage sampling. Data were collected through a structured questionnaire with a reliability coefficient of 0.87. The data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation, as well as inferential statistics using t-tests and ANOVA. The findings revealed that (1) the overall quality of life of the elderly rice farmers was at a moderate level ( = 3.76, SD = 0.86). The highest mean score was in the domain of personal beliefs and values ( = 3.94, SD = 0.76), followed by mental health ( = 3.67, SD = 0.85), independence ( = 3.68, SD = 0.85), and social relationships, while the environmental domain had the lowest score ( = 3.49, SD = 0.89). (2) Statistically significant differences in quality of life were found in relation to age (p = 0.47), chronic illness (p < .001), income (p = .015), and debt (p = .003), In contrast, gender, marital status, and total farming area showed no significant differences.